PERFORMANCES OF THE 3D STRAIN BASED FINITE ELEMENTS - MAALEM, T. (Courrier du Savoir; Vol. 11 (2011): Courrier du Savoir)
Some of the 3D strain based finite elements are presented shortly. They have eight nodes per element, except for the condensed one, whom have nine in the departure. Each of the nodes contains the three usual d.o.f., these elements were developed not only for the study of the 3D problems but also for the analysis of thin and thick plates. Among its, one has a regular shape, indeed the SBP8element (strain based parallelepiped 8 nodes) is presented in detail. Numerical examples show that it possesses properties of high accuracy, is capable of passing the various patch tests, and does not exhibit extra zero energy modes. It is free from locking for very thin plate analysis, and has better performance compared with his “congener” the conforming displacement element and some other 3D elements.